POTENSI PENINGKATAN NILAI EKOLOGI, SOSIAL DAN EKONOMI MASYARAKAT MELALUI PEMBANGUNAN JEJANGKIT ECOPARK BARITO KUALA - Arief Widya Hermas Panji; Agung Nugroho; Leila Ariyani Sofia; Noor Arida Fauzana (EnviroScienteae, 2022)
The 2019 Regional Revenue and Expenditure Budget is 67.34 billion Rupiah (while Banjarmasin City's Original Local Government Revenue is 1.5 Trillion Rupiah or only 0.04% of Banjarmasin's Original Local Government Revenue), the 'assistance' balance budget from the central government is amount 900 billion Rupiah/year. In 2020, Barito Kuala's Gross Regional Domestic Product (GRDP) 27.81% was contributed by the agriculture, forestry and fishery sectors, the processing industry contributed 15.76%. This research is interesting to carry out, how an area with minimal Original Local Government Revenue spends high costs not for the main sectors. In addition to using a large budget, and the construction of the Jejangkit Ecopark is carried out in areas that are continuously flooded. This study aims to analyze the potential for increasing the ecological, social, and economic value of the community through the construction of the Jejangkit Ecopark and designing strategic concepts in the development of the Jejangkit Ecopark area. The method used is a questionnaire used to find out how the community's perception of the activity, and interviews with Expert/Professional Judgment are used to obtain data that will be processed as the formulation of strategic concepts of SWOT analysis in the development of Jejangkit Ecopark. Considering the previous use as abandoned ex-World Food Day land which was claimed to be less productive, this activity is considered a positive hope for increasing environmental value in the area. The potential for improving ecology in overcoming the problem of the tendency for ecopark areas to flood, can be done on a micro and macro basis. This activity also improves the social and economic aspect development of the community, becomes a means of publicizing local agricultural culture, Ecosystem Recovery is a must in the development of an Ecopark, the recovered ecosystem will have a greater value for environmental services.